(untitled) (CAHIERS MAGELLANES-NS, 2024)
The term "user-generated content" (UGC) refers to the material that is created and shared by consumers and other users. UGC has become an increasingly essential tool in marketing for building brand awareness and engaging customers. The purpose of this research was to evaluate the connection between user-generated content (UGC) marketing and consumer engagement as it relates to the process of creating brand awareness. The approach consisted of doing a comprehensive evaluation of the relevant literature, with a particular emphasis on research that looked at how user-generated content (UGC) marketing influences consumer engagement and brand identification. According to the findings, marketing strategies based on user-generated content have a beneficial effect on consumer engagement and brand awareness. In addition, the research uncovered the many forms of user-generated content (UGC) that are the most successful in engaging consumers and developing brand awareness. These forms of UGC include customer reviews, posts on social media, and user-generated films. According to the findings of the research, organisations that want to boost consumer engagement and increase brand awareness might benefit from using marketing strategies that are based on user-generated content (UGC).